Neutral Three-coordinate Complexes of Mercury(II) Invohing Coordinated Cyano Groups - S. AHUJA , I.; Tripathi, Shailendra; Yadava, C.L. (Asian Journal of Chemistry, 2010)
1 : 1 Complexes of mercury(II) cyanide with 2-benzylpyridine, 4-picolylamine, 2-benzoylpyridine, 4-benzoylpyridine, 1,3-bis-(4-pyridyl) propane, quinoline, 6-methylquinoline; benzo(f)quinoline, isoquinoline, 3-methylisoquinoline, nicotinamide and N-methylnicotinamide have been synthesized. Molar conductances, molecular weight determinations and infrared spectral measurements down to 200 cm–1 show that all these compounds are neutral species having monomeric three-coordinated environments around mercury(II) in the solid state.